THU0457 Less than half of patients treated with high-dose allopurinol reach sua target. (15th June 2017) - Morlock, R; Taylor, DC; Baumgartner, S
Abstract : Background: Although allopurinol is FDA approved for up to 800 mg per day and EMEA authorized for up to 900 mg per day, most patients receive 300 mg per day or less. Objectives: To describe physician, patient, and treatment characteristics in gout patients treated with allopurinol and to assess the proportion of patients reaching serum uric acid (sUA) target by allopurinol dose. Methods: Patient data from a quantitative survey of physicians were utilized and results confirmed through chart review. Initial and current dose of allopurinol, presence of co-morbid conditions, sUA lab results, physician specialty, and patient characteristics were assessed. Data on number of patients achieving target sUA≤6mg/dL were also collected. Descriptive characteristics are presented as proportions or means and standard deviations (SD). Multivariate and descriptive statistics are used to describe patients with sUA≤6 mg/dL. Results: A total of 251 rheumatologists and 250 primary care physicians were interviewed. Of 2505 patients with gout, 1437 (57%) were treated with allopurinol. Use of high-dose allopurinol significantly differed by country with less than 6.5% of patients in France, Germany, and Spain given >300mg, whereas 10.2%, 19.5%, and 33.6% of patients in Italy, the US, and the UK, respectively, received a daily dose >300mg (p<0.01). Over 12 months the percentage of patients achieving sUA ≤6.0 mg/dL differed across the 6 countries. Looking across all countries, only 43.8% and 44.7% of patients achieved sUA <6.0mg/dL with 301–599mg and ≥600mg of allopurinol QD, respectively. A multivariable-adjusted model found patients with tophi (OR 3.42; p<0.01), co-existing alcoholism (OR 1.73; p<0.05), COPD (OR 2.01; p<0.05), smoking cessation treatment (3.49; p<0.05), and from the UK (OR 3.98; p<0.01) were more likely to be using >600mg of allopurinol. Regardless of allopurinol dose, the co-variates UK vs. other countries (OR 3.51; p<0.01), time on therapy >24 months (OR 1.39; p<0.01), and chart-documented co-existing hypertension (OR 1.36; p<0.05) were predictive of achieving sUA <6 mg/dL. Whereas physician sub-specialty [general practitioners vs. rheumatologists (OR 0.56; p<0.01)], having tophi (OR 0.72; p<0.05), and chart-documented co-existing alcoholism (OR 0.67; p<0.05), hyperlipidemia (OR 0.74; p<0.05), and kidney stones (OR 0.49; p<0.05) were found to be associated with not achieving sUA <6 mg/dL. After adjusting for confounding factors, over a 12-month period, there was no difference in achieving sUA <6 mg/dL for those treated with high- vs. low-dose allopurinol. Conclusions: Allopurinol is approved for up to 800mg in the US and 900mg in the EU but the majority of patients are treated with ≤300mg per day. Less than 50% of patients achieve sUA <6mg/dL at any dose of allopurinol. These data suggest a need for consideration of new treatment options on top of allopurinol for uncontrolled gout patients. Acknowledgements: This study was funded by Ironwood Pharmaceuticals. Disclosure of Interest: R. Morlock Consultant for: Received consulting fees from AstraZeneca and Ironwood Pharmaceuticals, and was a consultant of Ardea Biosciences, Inc, a member of the AstraZeneca Group, at the time of the research, D. Taylor Employee of: Employee of Ironwood Pharmaceuticals, S. Baumgartner Employee of: Formerly full-time employees of Ardea Biosciences, Inc., a member of the AstraZeneca Group